Personal Safety in Information Societies - A. Vorobyova, Olga; M. Snurnitsyna, Yulia; V. Nokhsorov, Vasiliy; A. Kolesnikov, Mikhail; Thanh Nguyen, Phong (International Journal of Psychosocial Rehabilitation, 2024)
The problem of information security in the modern information society is transformed into the problem of personal safety. The article deals with the problem of preserving the personality turned out to be multilayered and polyphonic, and the conditions that block the process of formation and transmission to future generations of the system of spiritual and cultural values that are basic for personality formation turned out to be too significant. The authors analyze the main channels operating in the information society, according to which an active destructive effect on the personality is possible. It is concluded that in the information space a truly effective system of preserving a person requires the formation of a new type of worldview, not destroying neither the spiritual nor the bodily foundations of personality. In parallel with the education system needs to form new channels of education and translation of spiritual and cultural values that meet the needs of post-industrial society.